Elaeagnus umbellata thunb. as the potential invasive species in Belgrade region - Skočajić Dragana; Grbić Mihailo; Tomićević Jelena; Đunisijević-Bojović Danijela; Đukić Matilda (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2008)
It is known that invasive plant species, as the species which most often spread and suppress the native species, form stable populations and become dominant firstly by occupying the sites of urban areas, and later on by continuing their invasion to the neighbouring suburban and rural areas. This paper presents the research of biological and ecological characters of Elaeagnus umbellata Thunb., one of the potential invasive species. The phenological observation of this species yield abundance and periodicity and the biometric analysis of fruits and seeds point to a high quality of its generative reproductive material. The analysis of seed dormancy of this species in our conditions, as the significant factor of the control of potential invasiveness, shows its double dormancy and its elimination requires combined chemical treatments and several months of stratification. The study of mechanisms of autumn olive dormancy breaking (overcoming the reproductive barrier) and seed dispersion (overcoming the dispersion barrier) is very significant for the forecast of further dispersion of this species.